The effects of regulatory performance on the debt-growth relationship: Cases of upper-middle-income economies - Nur Hayati Abd Rahman; Shafinar Ismail; Khairunnisa Abd Samad; Bestari Dwi Handayani; Yozi Aulia Rahman; Wijang Sakitri (Economies, 2022)
Upper-middle-income economies (UMIE) are experiencing an economic slowdown, partly due to weak regulatory performance. This issue leads to slow growth in private sector participation, thus limiting the ability to achieve higher economic growth. At this critical point, the government's role is to inject funds into economies, hoping that growth can be increased and sustained for an extended period. Nevertheless, injecting more funds through borrowings from external debt exposes economies to vulnerable conditions. Thus, this study aimed to examine how regulatory performance affects economic growth and moderates the debt-growth relationship in UMIE. By using the generalized method of moments (GMM) as an estimation method for 32 countries from 2004 to 2020, regulatory performance was found to adversely affect economic growth. Moreover, as regulatory performance improves, public debt is expected to enhance the economic growth of UMIE. These findings are novel, as they provide significant evidence for the importance of improving the regulatory performance of UMIE. Weak regulatory performance might force a government to become the engine of growth instead of the private sector, thus leading to the adverse effect of debt on growth in UMIE. These findings have to several policy implications, particularly regarding reducing bureaucracy and improving regulatory performance in UMIE. Future researchers could extend this study by comparing the results from different groups of economies or countries.
Keywords: 330; economic growth; external debt; GMM; marginal effects; regulatory performance